Jian-Pi-Yi-Shen Formula Improves Adenine-Induced Chronic Kidney Disease via Regulating Tryptophan Metabolism and Aryl Hydrocarbon Receptor Signaling - Liu, Xinhui; Deng, Ruyu; Chen, Yulian; Huang, Shiying; Lu, Jiandong; Zheng, Lin; Xiong, Guoliang; Li, Shunmin (Frontiers in Pharmacology, 2022)
Traditional Chinese medicine (TCM) is an important complementary and alternative branch of chronic kidney disease (CKD) therapy. Jian-Pi-Yi-Shen formula (JPYSF) is a TCM formula used for treating CKD with good efficacy. However, the underlying mechanisms of JPYSF in treating CKD remain to be elucidated. The purpose of the present study was to investigate the renoprotective effect and potential mechanism of JPYSF in treating CKD. CKD rat model was induced by feeding a diet containing 0.75% w/w adenine for 4 weeks. JPYSF was given by gavage every day, starting from the 3rd week of the adenine-containing diet and continuing for 6 weeks at the dose of 10.89 g/kg. Renal injury was evaluated by serum creatinine (Scr), blood urea nitrogen (BUN), histopathology, and fibrotic markers expression. Serum levels of tryptophan metabolites were detected by ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS). Aryl hydrocarbon receptor (AHR) signaling was tested by Western blot analysis. The results found that JPYSF treatment significantly lowered Scr and BUN levels, improved renal pathological injury, and down-regulated fibrotic markers expression in CKD rats. Furthermore, JPYSF significantly reduced the levels of 10 tryptophan metabolites in the serum of CKD rats and restored the level of tryptophan. Additionally, the kidney expression of AHR signaling was enhanced in CKD rats and was further suppressed in JPYSF treated rats. These results suggested that JPYSF protected against adenine-induced CKD via modulating tryptophan metabolism and AHR activation.